Concussion management and concussion recovery in Gaelic games: a qualitative analysis - Ed Daly; Lisa Ryan (Frontiers Media S.A., 2024)
BackgroundThe purpose of this qualitative research study was to interview current and retired Gaelic games athletes to understand the current landscape of concussion recovery in Gaelic sports from the athlete perspective.MethodsA grounded theory methodology was employed to explore the experiences of a cohort of Gaelic games athletes (n = 22) regarding recovery from concussion, the levels of concussion awareness in Gaelic sports and their opinions on current concussion identification protocols. The study's data were gathered through semi-structured interviews.ResultsTwo major themes were identified, (1) Male and female athletes experience a range of acute and chronic symptoms post-SRC and (2) Gaelic sports athletes are expected to demonstrate constant allegiance and commitment to the GAA. These themes were further divided into categories and subcategories.ConclusionBased on the experiences of the cohort of Gaelic sports athletes, there exists a wide variation of SRC symptomology in the acute, and chronic (post-concussion syndrome) phases. In many cases, there are reports of long-term side effects associated with the perceived mismanagement or misdiagnosis of SRC in Gaelic sports. Gaelic sports athletes require a more robust SRC management system to support and manage SRC in the acute, chronic and long-term phases.